An inconvenient truth: the complexity problem and limits to justice. (25th October 2019) - Risse, Jörg
Abstract: For years, the arbitration scene had to fight for lucrative, large-scale proceedings, which is no longer an issue today: arbitration as such has found its place in the legal landscape and has established itself as the means of choice. With the increasing complexity of the disputes and the high sums of money involved, however, the volume of the written submissions and the number of exhibits have exploded, sometimes to a previously unimaginable level. Tasked with reading 10, 000 pages of submissions plus reviewing thousands of exhibits, arbitral tribunals are pushed to their limits. Sometimes, proper adjudication of these super fact-rich and complex cases becomes virtually and physically impossible. The article describes the problem and reviews what can be done to cope with this inconvenient truth.